The Volatility and Risk-Return Trade-Off of Malaysian Islamic and Conventional Indexes During the Global Financial Crisis and COVID-19 Pandemic - Foo Siong Min; Nazrul Hisyam Ab Razak; Fakarudin Kamarudin; Nadisah Zakaria (Asian Journal of Business and Accounting, 2023)
Manuscript type: Research paper Research aims: This study aims to investigate the volatility characteristics and risk-return trade-off of Islamic and conventional indexes in the Malaysian market. Design/Methodology/Approach: The research covers the daily data of the period from August 2007 to December 2022, divided into four distinct periods: the full sample, the period during and after the 2007- 08 financial crisis, and the period during the COVID-19 pandemic. The research employs a hybrid model that combines ARIMA with GARCH family models. Research findings: In this research, both Islamic and conventional indexes in the Malaysian market demonstrate a memory effect, emphasising the persistence of market volatility through the influence of past volatility. Additionally, historical data, represented by lagged values, significantly shape volatility, while negative shocks have an immediate and pronounced impact compared to positive shocks, providing valuable insights for investors and risk management. Lastly, during the COVID-19 crisis, the conventional index showed no leverage effect, and the Islamic index lacked safe haven characteristics, making this crisis unique in the Malaysian financial context. Theoretical contribution/Originality: This research contributes to the understanding of market volatility dynamics in the Malaysian context by utilising a hybrid ARIMA-GARCH model. The identification of memory effects, asymmetric responses, and the unique characteristics observed during the COVID-19 crisis adds to the body of knowledge on financial market behaviour. Practitioner/Policy implication: The findings of this study have practical implications for investors and supervisory entities operating in the Malaysian market. Understanding the persistence of volatility and the differential impact of positive and negative shocks can help investors make more informed decisions, while regulators can use this information to quantify and manage market volatility effectively. Research limitation/Implications: The limitation of the present study is that the results may be influenced by the selection of the sample period, potentially yielding different outcomes depending on market conditions, such as the presence of bull or bear markets, periods of high or low volatility, or other contextual factors.